Enhancedanti-tumor efficacy through a combination of intramuscularly expressed DNA vaccine and plasmid-encoded PD-1 antibody - Liu, Xun; Yang, Yueyao; Zheng, Xiufeng; Liu, Ming; Wang, Gang (Frontiers in Immunology, 2023)
Immune check inhibitors (ICI) still have moderate response rates ( 20%-30%) in some malignancies clinically, and combinations with other immunotherapeutic strategies including DNA tumor vaccines have been considered to potentially optimize the efficacy of cancer treatment. In this study, we validated that intramuscular injection of plasmid DNA (pDNA) encoding OVA combined with pDNA encoding α-PD-1(abbreviated as α-PD-1 in the following treatment groups ) may enhance the therapeutic efficacy by means of in situ gene delivery technique and enhanced muscle-specific potent promoter. Mice treated with pDNA-OVA or pDNA-α-PD-1 alone showed weak tumor inhibition for MC38-OVA bearing model. In comparison, combined treatment of pDNA-OVA and pDNA-α-PD-1 showed superior tumor growth inhibition and significantly improved survival rate over 60% on day 45. In the B16-F10-OVA metastasis model, the addition of DNA vaccine enhanced resistance to tumor metastasis and increased the population of CD8+ T cell in blood and spleen. In conclusion, the current research showed that the combination of DNA vaccine and pDNA-encoded PD-1 antibody expressed in vivo was an efficient, safe, and economical strategy for tumor therapy.